An Investigation into Major Causes for Postharvest Losses of Horticultural Crops and Their Handling Practice in Debre Markos, North-Western Ethiopia - Yebirzaf Yeshiwas; Esubalew Tadele (Advances in Agriculture)
In developing countries, food systems are mainly characterized by unorganized, traditional supply chains, and limited market infrastructure. Bulk quantity of the harvested produce is lost every year because of the absence of proper postharvest handling and management practices. The current study was conducted to estimate and identify the major causes for postharvest losses of fruits and vegetables in Debre Markos, north-western Ethiopia. Forty respondents who were retailing fruits and vegetables were randomly selected and qualitative and quantitative data were collected by using direct market observation and semistructured questioners. The result of the present study revealed significant differences between sociodemographic factors, handling practices, and postharvest loss. Educational status, selling experience, and packaging material have a significant relationship with postharvest loss. A significant difference was obtained among the transportation methods used, the selling place, storage methods, and materials. The result also indicated that fewer than 20 percent of respondents practiced selling fruits and vegetables in the resident mini shop. The majority of damaged produce was sold at a discount price. Retailers do not have formal knowledge of postharvest handling practices. The average postharvest losses of fruits and vegetables were estimated to be five to eighty-three percent of the market share. Mainly, during retailing, rotting, mechanical damage, poor handling, improper management of temperature and relative humidity, and hygiene problems during handling are among the major causes of postharvest losses. To reduce the high postharvest loss and supply quality products for consumers throughout the year, intervention activities such as the construction of permanent selling place for perishables, practicing various evaporative cooling technologies, outset training, awareness creation, and infrastructures should be effectively and urgently addressed.